PERBANDINGAN IMPLEMENTASI METODE WEIGHTED MOVING AVERAGE DAN METODE SINGLE EXPONENTIAL SMOOTHING PADA PENENTUAN PERSEDIAAN OBAT - Aprilyanta, I Gede Bawa; Ariesta Lestari; Sherly Christina (STMIK Palangkaraya, 2022)
Pharmacy is a business-oriented business which directly sells medicines to consumers. In ensuring that the drug supply is in accordance with market demand, the leadership of the Hasanah Palangka Raya Pharmacy usually estimates the drug supply for the future period based on sales reports and experience. For research purposes, it will provide a solution by developing Forecasting Applications by applying the Weighted Moving Average method with weights 2, 3, 4, 5, 6, 7, 8 and 9 periods and the Single Exponential Smoothing method with constant smoothing or (alpha), namely 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 and 0.9. The results of the study resulted in the Weighted Moving Average method as the method that has the smallest Error value where from the 4 drugs that were used for forecasting, 3 drugs showed the Weighted Moving Average method as the best method which has the smallest Mean Absolute Deviation value and the smallest Mean Absolute Percentage Error value compared to Single Exponential Smoothing.